2021
DOI: 10.1101/2021.11.16.468793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrochemical biosensors based on peptide-kinase interactions at the kinase docking site

Abstract: Kinases are important cancer biomarkers and are conventionally detected based on their catalytic activity. Kinases regulate cellular activities by phosphorylation of motif-specific multiple substrate proteins, resulting in lack of selectivity of activity-based kinase biosensors. We present an alternative approach of sensing kinases based on the interactions of their allosteric docking sites with a specific partner protein. The new approach was demonstrated for the ERK2 kinase and its substrate ELK-1. A peptide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To determine whether the D domain peptides that bound ERK2 can also inhibit its interactions mediated via its DRS, we used an electrochemical impedance spectroscopy (EIS)‐based ERK2 detection assay developed in our labs [29] . The assay was comprised of the ELK1 D domain peptide, ELK1 312–321, adsorbed onto gold electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine whether the D domain peptides that bound ERK2 can also inhibit its interactions mediated via its DRS, we used an electrochemical impedance spectroscopy (EIS)‐based ERK2 detection assay developed in our labs [29] . The assay was comprised of the ELK1 D domain peptide, ELK1 312–321, adsorbed onto gold electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…To conclude, we showed that inhibition of ERK2 can be done by using peptides that target the PPI of its DRS docking site [29] . This approach is highly versatile and can easily be utilized for different kinases and other types of enzymes, whose activities are crucial in disease.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations